Evaluation of Superabsorbent Hydrogel Composites Based on Carrageenans-Graft-Poly(sodium acrylate)/Kaolin - Soleimani, Fatemeh; Sadeghi, Mohammad; Shahsavari, Hadis (Asian Journal of Chemistry, 2012)
Graft copolymerization of acrylic acid in presence of kaolin powder using methylenebisacrylamide as a crosslinking agent and ammonium persulfate as an initiator was carried out under argon atmosphere in a homogeneous aqueous medium onto kappa-carrageenan. A plausible reaction mechanism of grafting has been suggested. The morphology of the samples was examined by scanning electron microscopy. The composite structure was confirmed using FTIR spectroscopy. A new absorption band at 1707 cm-1 in the composite spectrum confirmed kaolin-organic polymer linkage. According to the empirical rates of the polymerization and the graft copolymerization of acrylic acid onto carrageenan backbone, the overall activation energy of the graft copolymerization reaction was estimated to be 17.33 kJ/mol.